VD_FINDINFO HC / 2009 / 402 vom 26. März 2009 - VD Tribunal cantonal (2009)
INSOUMISSION À UNE DÉCISION DE L'AUTORITÉ, FIXATION DE LA PEINE, SURSIS À L'EXÉCUTION DE LA PEINE | 292 CP, 44 CP, 47 CP, 411 CPP